Pelatihan pembuatan soal berbasis HOTS bagi guru di SD Inpres Galangan Kapal IV Kota Makassar - Amrah Amrah; Nurhaedah Nurhaedah; Lutfi Lutfi; Erma Suryani (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
This activity aims to improve teachers’understanding SD Inpres Galangan Kapal IV on HOTS basedquestions and implement them in making questions. Theactivities in this training are 1) understanding the importanceof HOTS-based questions, 2) exploring the correct techniquesin making HOTS-based questions, and 3) practicing makingHOTS-based questions. The results of this training showedthat 1) the training was conducted at SD InpresGalanganKapalIV Tallo district of Makassar; 2) Observating the orientation tothe problems faced by the teachers regarding making HOTSquestions; 3) Lecture session was conducted to introduce somematerials about the essentials and importance of HOTSquestions; 4) Demonstration in giving direct practice toparticipants in making HOTS questions. The result is that theprogram is carried out smoothly as planned, participants showserious interest and attention to the training, teaching andapplication materials for making HOTS-based questions.